Causal Relationship between Trade Openness and Economic Growth: A Panel Data Analysis of Asian Countries - Alam, Khandaker Jahangir; Sumon, Khairul Kabir (International Journal of Economics and Financial Issues, 2019)
This paper examines the causal relationship between economic growth and trade openness for 15 Asian countries over period 1990–2017. We have applied panel cointegration and causality approaches to examine the long-run and causal relationship between variables. Empirical results confirm the presence of cointegration between variables. The impact of trade openness on economic growth is found to be positive. The panel VECM Granger causality analysis reveals the bidirectional causality between economic growth and trade openness. Keywords: Trade Openness, Economic Growth, Panel Cointegration, Causality. JEL Classifications: F11, F14, F43, C23 DOI: https://doi.org/10.32479/ijefi.8657